Morphological data support the recognition of four species in the genus Sirystes Cabanis & Heine, 1859 (Aves: Tyrannidae) - Lopes, Leonardo Esteves; Gonzaga, Luiz Pedreira (Zootaxa, 2016)
Sirystes is a widespread genus in the Neotropical region. Historically, five subspecies were recognized in a single widespread species, but more recently four separate species have been recognized, based on vocalizations and limited morphological data. In this paper, we analyze individual and geographic variation in this genus on the basis of body measurements and plumage coloration of 514 specimens, including all name-bearing types available. We conclude that the four recently proposed species, S. sibilator, S. albogriseus, S. albocinereus, and S. subcanescens, can also be diagnosed by morphological data, corroborating more recent taxonomic treatments. We identified possible hybrids between S. sibilator and S. albocinereus from a narrow zone of contact in central Bolivia. We show that Sirystes sibilator atimastus Oberholser, 1902 represents a point on a cline within S. sibilator (Vieillot, 1818), and it is here regarded as a subjective junior synonym of the latter. We also provide new observations on the range and diagnosis of S. subcanescens, a name that has been frequently misused, and present a redescription of the four recognized species, as well as reviewing their range and natural history.